(untitled) (Biological Sciences - PJSIR, 2022)
The classical theory of collisional broadening and shift parameter ( , 8) of an isolated spectral line is used to obtain simple analytical formulas for calculating both and 8. These formulas are obtained on the assumption that the short range interaction is effective only in the broadening while the long range is effective in the shift of the spectral line. The parameters and 8 depend on the Weisskopfphase shift’ll" = I. The obtained formulas are applied to both vandervaals and Lennard - jones model potentials for some atomic pair interactions. The obtained results are in close agreement with the numerical results obtained before. This verify the validity of both of the Weisskopf phase shift and the obtained analytical formulas.